ANALISIS KADAR NPK KOMPOS BULU AYAM DAN SEKAM PADI DENGAN FERMENTOR PUMAKKAL SEBAGAI SUMBER BELAJAR BIOLOGI BERUPA LEMBAR KEGIATAN PESERTA DIDIK - Vina Yulita; Suharno Zen; Agus Sutanto (EDUBIOLOCK, 2024)
This research aimed to find out which dose of waste affects the levels of N, P, K in solid compost of chicken feather waste and rice husk, to find out the pumakkal formula and the dose of waste that was by the Indonesian National Standard (SNI) as a composting material to support learning biology. This type of research was experimental research by using the dose of chicken feather waste P0 (1.50kg), P1 (1.50kg), P2 (1.75kg), and P3 (2kg). The parameters observed were the content of Nitrogen (N). Phosphorus (P), and Potassium (K). Analyzed using a qualitative method by comparing the results with SNI solid compost. Based on the results of the study, there was an effect of the dose of chicken feather waste on compost. testing with solid compost SNI shows that (P0) is 35.503%, then in treatment 1 (P1) is 35.012%, treatment 2 (P2) is 35.947% and in treatment 3 (P3) is 36.941%. The results of this study can be utilized as a learning resource in the form of Learner Activity Sheets and are suitable for use as a class XII biology learning resource. With a validation value in the material aspect of 71.1%, the design aspect of 87.5%, and the language aspect of 70%.